Effect of race and sex on lupus diagnosis in primary care: A randomized factorial survey study - Alyssa Howren; Quan L. Tran; Sadaf Sediqi; Saadiya Hawa; Douglas K. Owens; Eleni Linos; Titilola O. Falasinnu; Yashaar Chaichian; Julia F. Simard (PLoS ONE, 2026)
Background Systemic lupus erythematosus (SLE) is a heterogeneous autoimmune rheumatic disease whose epidemiology and clinical prognosis vary by race and sex. Observed disparities in SLE may be partly attributable to cognitive processes in clinical decision-making, which can influence diagnostic accuracy and clinical management. We aimed to examine variation in primary care physicians’ (PCP) diagnosis and management of SLE when all content of a clinical case is identical, apart from race and sex. Methods We distributed an online randomized factorial survey from 04/11/2024–06/10/2024 to PCPs across the US. Participants were presented with one of four possible SLE vignettes – Black female, White female, Black male, White male – for which all other clinical content was identical. Block randomization was used to randomly modify the race (Black/White) and sex (female/male) of the SLE “case”. Primary outcomes were correct text-based responses for SLE diagnosis at initial case presentation and after reviewing additional lab results. Secondary outcomes were participants’ review time and planned next steps (treatment, referral, tests) as a proxy for cognitive bias and certainty, respectively. We calculated descriptive statistics for all outcomes stratified by assigned randomized factor and used chi-square tests to evaluate between-group differences. Results 1031 PCPs (42.7% women, mean age 52.1 ± 12.1 years) completed the case. At initial presentation, 63.9% of participants correctly identified SLE as a differential diagnosis. An initial diagnosis of SLE significantly differed by the race and sex of the case (p < 0.001), with the highest proportion of correct diagnoses occurring for Black female cases (72.2%) and lowest for White male cases (55.3%). Median review time for correct initial diagnoses was longest for White male cases (175 s). After participants reviewed lab results, the overall proportion assigning a final diagnosis of SLE (63.9%) remained unchanged from the initial diagnosis. Conclusion A patient’s race and sex may influence diagnostic accuracy and clinical decision-making for SLE in primary care. The observed variation in diagnostic accuracy, which aligns with the descriptive epidemiology of SLE, highlights the need for targeted interventions to ensure equitable diagnostic processes.